Limits and Practical Aspects of Social Media Use in Police Sting Operations in Sexual Exploitation of Minors Crimes. Polish Practice and the American Perspective - Stromczyński, Błażej (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article discusses the legal grounds, limitations and practical aspects of police undercover operations conducted on social media to prevent online-facilitated sexual abuse of children. The author analyzes the regulations of the criminal code and judiciary regarding grooming, which lately became famous especially in relation to the activities of the so-called pedophile hunters. Next, the key aspects and legal limits of sting operations in Polish law are analyzed. Later, the place and role of the undercover operations and entrapment doctrine in American law is compared to Polish practice. Finally, the best practices and key rules of operational security that should be applied when conducting this undercover online activity.